Self-Esteem As A Mediator In Parental Attachment And Life Satisfaction In Adolescence - Puspitahati, Claudia Maharani; Widyorini, Endang (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2025)
One of the expectations of very individual including teenagers is the achievement of life satisfaction. However, not all teenagers are capable to achieve their life satisfaction. In Indonesia, the level of life satisfaction is still relatively low. The purpose of this study is to look the effect of parental attachment on life satisfaction with self-esteem as a mediator in one of the private Junior High Schools in Kudus. The hypothesis proposed is that self-esteem plays a mediator role in the influence of parental attachment on adolescent life satisfaction. This study uses a quantitative approach, with a sample of 128 students selected through total sampling techniques. The measurement instruments used include Inventory Parent and Peer Attachment (IPPA), Satisfaction With Life Scale (SWLS), and Rosenberg Self-Esteem Scale (RSES). Mediation analysis uses the SEM mediation analysis featured of JASP software version 16.1. The outcome showed that parental attachment had a significant effects on life satisfaction directly with a value of 0,001 (p <0,05). Then the indirect of parental attachment on life satisfaction and self-esteem as mediators was obtained with a value of p 0,001 (p <0,05), which means that self-esteem can play a mediator between parental attachment and life satisfaction. The influence of parental attachment and self-esteem together on life satisfaction was 98,3%.Salah satu keinginan yang diharapkan setiap individu termasuk remaja adalah mencapai life satisfaction. Namun tidak semua remaja mampu mencapai life satisfactionnya. Di Indonesia sendiri tingkat life satisfaction masih tergolong dalam kategori rendah. Tujuan penelitian ialah untuk melihat pengaruh parental attachment terhadap life satisfaction dengan self-esteem sebagai variabel mediator pada salah satu SMP swasta di Kudus. Adapun hipotesis yang diajukan yaitu self-esteem berperan sebagai mediator pada pengaruh parental attachment terhadap life satisfaction remaja. Penelitian ini menggunakan pendekatan kuantitatif, dengan sampel yang digunakan sebanyak 128 siswa/siswi yang dipilih melalui teknik sampling total. Alat ukur yang digunakan meliputi Inventory Parent and Peer Attachment(IPPA), Satisfaction With Life Scale (SWLS), dan Rosenberg Self-Esteem (RSES). Analisis mediasi menggunakan fitur SEM mediation analysis dari software JASP versi 16.1. Hasil penelitian memperlihatkan bahwa parental attachment berpengaruh signifikan terhadap life satisfaction secara langsung dengan nilai p 0,001 (p <0,05). Kemudian pengaruh tidak langsung parental attachment terhadap life satisfaction dan self-esteem sebagai mediator diperoleh nilai p 0,001 (p <0,05), yang berarti self-esteem dapat berperan sebagai mediator antara parental attachment dan life satisfaction. Besar pengaruh parental attachment dan self-esteem secara bersama-sama terhadap life satisfaction sebesar 98,3%.